1993
DOI: 10.1007/bf00230202
|View full text |Cite
|
Sign up to set email alerts
|

Changes induced in the representation of auditory space in the superior colliculus by rearing ferrets with binocular eyelid suture

Abstract: There have been conflicting reports concerning the importance of visual experience in the development of auditory localization mechanisms. We have examined the representation of auditory space in the superior colliculus of adult ferrets that were visually deprived by binocular eyelid suture from postnatal days 25-28, prior to natural eye opening, until the time of recording. This procedure attenuated the transmission of light by a factor of a least 20-25 and blurred the image so that, as long as the eyelids we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 49 publications
8
85
0
Order By: Relevance
“…Dark-rearing experiments in rats demonstrated that visual experience is important for maintenance but not for the development of the visual map in the SC (Carrasco et al 2005). Similarly, in barn owls and ferrets, visual manipulations such as blind (sutured eyelids) or prisms-rearing had very little effect on the visual space map (Knudsen et al 1991;Feldman and Knudsen 1997;King and Carlile 1993).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Dark-rearing experiments in rats demonstrated that visual experience is important for maintenance but not for the development of the visual map in the SC (Carrasco et al 2005). Similarly, in barn owls and ferrets, visual manipulations such as blind (sutured eyelids) or prisms-rearing had very little effect on the visual space map (Knudsen et al 1991;Feldman and Knudsen 1997;King and Carlile 1993).…”
Section: Discussionmentioning
confidence: 98%
“…More direct evidence for the involvement of sensory experience has been achieved through long-term manipulation experiments, such as earplug, blind, and dark rearing. Visual deprivation studies have demonstrated an abnormal alignment of the auditory map with the visual map in ferrets (King and Carlile 1993) and barn owls (Knudsen et al 1991) but mostly normal auditory receptive fields. The effects of earplugs on barn owls have been a frequency-dependent compensating shift in the tuning of neurons (Mogdans and Knudsen 1992;Gold and Knudsen 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of visual inputs by binocular eyelid suture in young ferrets (King and Carlile 1993) and owls caused abnormalities in the organization of the auditory space map in the SC. In guinea pigs, dark rearing, which completely eliminates all visual information, was found to result in dSC cells with broad auditory spatial receptive fields and an auditory representation that showed little or no topographic order (Withington et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this previous work has focussed on developmental adaptive changes and on the alignment of auditory and visual representations at the neuronal level (e.g. ferret: King et al 1988;King and Carlile 1993;barn owl: Knudsen and Brainard 1991). In general, there is a significant amount of evidence for interactions between the visual and auditory modalities that could point to visual inputs as a functional basis for auditory recalibration (see King 2009 for review).…”
Section: Introductionmentioning
confidence: 99%